2017
DOI: 10.1111/inm.12401
|View full text |Cite
|
Sign up to set email alerts
|

Stigma of mental illness and substance misuse in sub‐Saharan African migrants: A qualitative study

Abstract: Stigma of mental illness and substance misuse can deter help seeking, especially in immigrants who are often reluctant to seek help early for these issues. The aim of the present study was to explore the stigma experience surrounding mental illness and substance misuse, and its implications for improving help seeking, for youths and parents from sub-Saharan African immigrant communities. A qualitative, descriptive design was used. Individual interviews were undertaken with 28 youths, and focus group discussion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 42 publications
2
48
0
Order By: Relevance
“…Cultural attitudes and religious beliefs surrounding disease etiology and treatment efficacy may delay presentation to care [21][22][23]. Stigma has been consistently identified as a barrier to HIV testing and treatment [24][25][26][27] as well as to uptake of mental health services [28,29]. Linguistic differences [5,30,31], legal status [32], cost [21], and provider discrimination [21,22] may also impede effective care.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural attitudes and religious beliefs surrounding disease etiology and treatment efficacy may delay presentation to care [21][22][23]. Stigma has been consistently identified as a barrier to HIV testing and treatment [24][25][26][27] as well as to uptake of mental health services [28,29]. Linguistic differences [5,30,31], legal status [32], cost [21], and provider discrimination [21,22] may also impede effective care.…”
Section: Introductionmentioning
confidence: 99%
“…Such research revealed that the general public frequently label PMHP as dangerous, blameworthy, incompetent and weak, which is often accompanied with emotions of fear and anger and can lead to behavioural intention of avoidance, punishment, and coercion [ 9 12 ]. Further, the literature shows that internalisation of public stigma or self-stigma is also frequent among PMHP, which reduces self-esteem, causes social isolation, and inhibits help-seeking behaviour [ 6 , 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this was a highly selected, convenience sample with the well-documented limitations for generalizability of such sampling methods (Schlenger, Jordan, Caddell, Ebert, & Fairbank, 2004). Indeed, only a small fraction of forcibly displaced persons receive any mental health treatment, because they often face socio-cultural stigma and limited access to health services in high- and low-income countries (McCann, Renzaho, Mugavin, & Lubman, 2018; Miller & Rasco, 2004). Likewise, limited range and variability of symptoms among treatment seekers may systematically limit the generalizability of such network data.…”
mentioning
confidence: 99%